RESPON KECEPATAN TIMBULNYA ESTRUS DAN LAMA ESTRUS PADA BERBAGAI PARITAS SAPI BALI SETELAH DUA KALI PEMBERIAN PROSTAGLANDIN F2α (PGF2α) - Ulvi Fitri Handayani; Madi Hartono; Siswanto . (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This research aims to response of onset estrus and estrus duration at various parity Bali cattle aftertwice injection of prostaglandin F2α (PGF2α). This research has been done in the Sukoharjo 2,Pringsewu District. The material is used as much as 12 cows, and the average weight rangeaverage cow is 285 kg. Methods of research used Completely Randomized Design (CRD) withthree treatments, they are (P0), (P1) and (P2). Each other treatment was repeated four times, theyare 4 Bali cattle parity 0 or heifers, 4 Bali cattle 1 or cow that has begat 1 times, and 4 Bali cattleparity 2 or cows that have been lambing 2 times. Hormone’s name is prostaglandin F2α (Juramate®) at a dose of 2 ml / tail. The results showed that there were highly significant differences(P<0.01) in the treatment of P0 and P1 to P2, but no effect between P0 and P1 to speed the onsetof estrus, and the differences were highly significant (P <0.01) between treatment on P0, P1, andP2 to the long estrus. The average respon of onset estrus for each successive treatments are P0 =44.15 hours; P1 = 48.89 hours; P2 = 22.33 hours. The average of estrus duration areRespectively : P0 = 12.94 hours; P1 = 20.85 hours; P2 = 16.63 hours.